Improvement of marital intimacy scale and a study of this instrument on measuring the result of psychotherapy - Makmuri Muchlas, Makmuri Muchlas (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Muchlas 1 has adapted marital intimacy scale (10 questions) from 36-items of PAIR (Personal Assessment of Intimacy in Relationships) to suit with Javanese culture. In his dissertation, the scale was used to describe that one of the ways to increase the condition of mental health of mothers attending a course on mental health is by improving their marital intimacy. The result is not like what was expected, although the scale had been approved in the reliability and validity test. In his study on this scale, Sudiyanto2 said that although it had significant validity, the scale still had low internal consistency; there were normative questions, asking about morality instead of intimacy; several statements were inappropriate and the ten questions might not represent marital intimacy dimensions. The demand to revise this scale became urgent, as the scale is the only one planned for Indonesians and its practicality is required to evaluate the results of consultations on marital problems as well as mental health conducted by existing institutions, especially the Advisory Board of Marital and Separation Problems (BP4). Later Muchlas and Sudiyanto3 revised this scale of marital intimacy, and it became the revised scale of Marital Intimacy (15 questions). This new scale had better validation and internal consistency. In this study the revision of the scale of marital intimacy was used to measure the marital intimacy of worried patients who visited BP4 for consultation concerning with their separaty. Through an experimental study using psychotherapy, 100 random samples were divided into two groups; 50 samples belonged to a group provided with psychotherapy and 50 other samples belonged to a control group without psychotherapy. Their marital intimacy was measured using the new instrument before and after they wereÂ provided with psychotherapy. The result showed significant difference between the two groups and the validity of the marital intimacy scale used in this study was adequately good.Keyword : marital intimacy -- validity of the MIS -- REMIS -- psychotherapy